2017
DOI: 10.1007/s00122-017-2992-3
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of QTL qCTB10-2 that confers cold tolerance at the booting stage in rice

Abstract: The QTL qCTB10 - 2 controlling cold tolerance at the booting stage in rice was delimited to a 132.5 kb region containing 17 candidate genes and 4 genes were cold-inducible. Low temperature at the booting stage is a major abiotic stress-limiting rice production. Although some QTL for cold tolerance in rice have been reported, fine mapping of those QTL effective at the booting stage is few. Here, the near-isogenic line ZL31-2, selected from a BCF population derived from a cross between cold-tolerant variety Kunm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Co-localized and pleiotropic M-QTLs located in adjacent regions on the chromosome govern multiple traits, which are most prominent for the concurrent improvement of multiple traits (Shakiba et al 2017;Li et al 2018;Liang et al 2018). In this study, eight clusters of M-QTLs or pleiotropic M-QTLs were identified on different chromosomes governing simultaneously different traits: .…”
Section: Phenotypic and Genotypic Variation Of Lts Tolerance Traitsmentioning
confidence: 74%
See 2 more Smart Citations
“…Co-localized and pleiotropic M-QTLs located in adjacent regions on the chromosome govern multiple traits, which are most prominent for the concurrent improvement of multiple traits (Shakiba et al 2017;Li et al 2018;Liang et al 2018). In this study, eight clusters of M-QTLs or pleiotropic M-QTLs were identified on different chromosomes governing simultaneously different traits: .…”
Section: Phenotypic and Genotypic Variation Of Lts Tolerance Traitsmentioning
confidence: 74%
“…These co-localized QTLs were identified in earlier studies on cold tolerance germination and yield component traits in rice (Andaya and Mackill 2003a, b;Koseki et al 2010;Wang et al 2016a;Shakiba et al 2017). Several major lowtemperature germination and seedling-stage QTLs have been distributed widely on all 12 chromosomes using bi-parental mapping populations and diverse rice genetic resources (Teng et al 2001;Chen et al 2006;Liang et al 2006Liang et al , 2018Fujino et al 2008;Pan et al 2015;Jiang et al 2017;Shakiba et al 2017;Li et al 2018). Among the total of 82 M-QTLs, 67% of the M-QTLs received favorable alleles from donor parent HNG, which is significant in LTS tolerance.…”
Section: Phenotypic and Genotypic Variation Of Lts Tolerance Traitsmentioning
confidence: 86%
See 1 more Smart Citation
“…Of these, 108 QTLs for CT were detected at the booting stage ( S1 Table ). Four QTLs, qCT8 , qCTB7 , qCTB3 and qCT-3-2 , have been fine mapped [ 6 , 11 13 ], qCTB10-2 was delimited to a 132.5 kb region containing 17 candidate genes and 4 genes were cold-inducible [ 14 ], and only two CT QTL, Ctb1 and CTB4a , have been cloned and functionally characterized [ 15 , 16 ]. Ctb1 encodes an F-box protein and functions as part of the E3 ubiquitin ligase complex that is associated with increased spikelet fertility (SF) under cold stress [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, rice seedlings exposed to low temperatures exhibit slow development, reduced tillers, yellowish leaves, and rot (Andaya and Mackill 2003). Furthermore, at the reproductive stage, intolerable cold negatively affects panicle growth, fertility and thus results in yield reduction (Li et al 2018). In sum, due to cold stress, rice cannot be grown on approximately 7,000,000 hectares of land in South and Southeast Asia (Sthapit and Witcombe 1998).…”
Section: Introductionmentioning
confidence: 99%